(untitled) (Indonesian State Law Review (ISLRev), 2021)
This research paper discusses the Child labor protection law, specifically in culinary business. The Author raises a phenomenon regarding a Child with initials JS who built Tang Kitchen culinary business along with his brother in Surabaya. Research method used is a Normative Juridical method, that processes legal material collected through literature review. This study aims to discover applicable law (legal protection) towards Children working in culinary business, particularly based on Act No. 13 year 2003 concerning Employment, Art No. 23 year 2002 concerning Children Protection and Art No. 35 year 2014 regarding Amendment of Art No. 23 year 2002 concerning Children Protection (Art No. 35 year 2014). The research result shows that JS and his Brother who are still classified as Children, have received a protection from Indonesian applicable law protection based on Article 69 and 71 of Act No. 13 year 2003 regarding Employment. Moreover, JS’ job in Tang Kitchen culinary is not considered as a job that endangers Children as regulated under KEPMENAKERTRANS 235/2003, and has complied with JS’ talents and interests as regulated under KEPMENAKERTRANS 115/2004.